How to lead academic departments successfully - Lindgreen, Adam; Irwin, Alan; Poulfelt, Flemming; Thomsen, Thyra Uth; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2021)
"It is an old cliché that leading and managing academics is like herding cats. This book challenges this myth and presents a way to deal with the many challenges of academic leadership, from managing departments, research groups and teams to managing tensions between research and teaching. The book is a practical and stimulating guide to different pathways to successful academic leadership, both in personal and organizational terms. Including reflections and advice from experienced leaders, this book provides ideas and guidance to help current and aspiring leaders increase their own efficiency and effectiveness across the following areas: Dealing with conflict Engendering team spirit Ensuring diversity and inclusion Leading change in business schools Leading research groups Creating a triple crown business school Collaborating with other disciplines and practitioners. An experienced group of contributors reflects on their own successes and failures to shine new light on academic leadership to support your own sense of success as a practicing or aspiring departmental head. We also hope that this book will be instructive for those who simply want to understand how this crucial aspect of academic life operates"--
Contents: Introduction to how to lead academic departments successfully -- Part I: Challenges of being an academic leader -- 1. On the particular challenges of managing professionals / Flemming Poulfelt -- 2. Relevant leadership: The dynamic equilibrium of managing and leading academic departments / Rickie A. Moore -- 3. The role of academic leaders of a business school: An internal tensions perspective / Matthew J. Robson -- Part II Transformational and performance leadership -- 4. The head of department as the key transformational leader / Asbjørn Busk J. and Søren Barlebo Rasmussen -- 5. Leading with purpose: Developing the first business school for public good / Martin Kitchener -- 6. Leading academic departments / Rob Goffee and Gareth Jones -- 7. Individual performance management: Enabler or threat to academic performance? / Andreas Werr and Katja Einola -- 8. Deploying systems thinking to create a 'triple-crown' business school / Michael C. Jackson OBE -- Part III Inclusivity, team spirit and career development -- 9. 'Don't think you can be everyone's friend': Dealing with conflict in an academic department / Alan Irwin -- 10. Smells like team spirit: A user's guide for department heads / Peter Kjær -- 11. 'Now you see it': Gender, inclusion and diversity / Maja Horst -- 12. Leading faculty as teachers / Hanne Andersen -- 13. Inclusive onboarding in academic departments / Daniel J. Petzer, Nicola S. Kleyn and Michele Ruiters -- Part IV Building, leading and funding research groups -- 14. Building research groups / Adam Lindgreen, C. Anthony Di Benedetto, Roderick J. Brodie and Peter Naudé -- 15. Dilemmas in university management: The case of copenhagen business school / Nanna Mik-Meyer -- 16. Pathways to external funding at departments: How to strengthen a change of culture by empowerment, supportive organizing and leadership? / Enno Hofeldt -- Part V Collaboration with other disciplines and practitioners -- 17. Collaborating with practitioners / C. An
Includes bibliographical references and index.
Description based on print record.
Keywords: elektronické knihy; electronic books; Educational leadership